Enhancement of polarization property of silane-modified BaTiO3 nanoparticles and its effect in increasing dielectric property of epoxy/BaTiO3 nanocomposites - Thi Tuyet Mai Phan (Journal of Science: Advanced Materials and Devices, 2016)
The surface modification of synthesized nano-BaTiO3 particles was carried out using γ-aminopropyl trimethoxy silane (γ-APS) in an ethanol/water solution. The modified particles were characterized by FTIR, TGA, surface charge analysis, and by dielectric constant measurement. The silane molecules were attached to the surface of BaTiO3 particles through SiOBaTiO3 bonds. The γ-APS grafted on BaTiO3 made the dielectric constant of the particles increase at frequencies ≥0.3 kHz in a wide range of temperature (25 °C–140 °C), due to the presence of NH2 groups. The dependence of the polarization vs. electrical field was measured in order to elucidate the dielectric behavior of the silane treated BaTiO3 in comparison to untreated BaTiO3. The nanocomposite based on epoxy resin containing BaTiO3 nanoparticles untreated and treated with γ-APS was also prepared and characterized. The results indicated that the γ-APS-modified BaTiO3 surfaces significantly enhanced the dielectric property of the nanocomposite.